Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5306/wjco.v10.i2.67
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer screening in patients with presumed branch-duct intraductal papillary mucinous neoplasms

Abstract: Because delayed diagnosis is one of the causes of poor prognosis in pancreatic ductal adenocarcinoma (PDAC), early detection is a key for overall improvement of prognosis. Towards this end, periodic screening is recommended for individuals considered high-risk for PDAC. Advances in diagnostic imaging modalities have increased the frequency of incidental findings of pancreatic cysts, including the intraductal papillary mucinous neoplasm (IPMN) - a major risk factor of PDAC, having 1% annual prevalence of concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In fact, the clinical guidelines focusing primarily on cyst morphology and stability to titrate surveillance are further complicated by the increasingly recognized risk of concomitant pancreatic ductal adenocarcinoma (PDAC) arising elsewhere in the pancreatic gland in patients with IPMN. 16,17 Concomitant PDAC in the setting of IPMN malignancy was originally reported to have a low incidence of between 2% and 7% in most surgical series. 16 However, more recent data suggest that the rate could be as high as 18% (from molecular pathology series) and 28% (from surgical series).…”
Section: Does Pancreatic Cyst Stability Justify Stopping Intraductal mentioning
confidence: 99%
“…In fact, the clinical guidelines focusing primarily on cyst morphology and stability to titrate surveillance are further complicated by the increasingly recognized risk of concomitant pancreatic ductal adenocarcinoma (PDAC) arising elsewhere in the pancreatic gland in patients with IPMN. 16,17 Concomitant PDAC in the setting of IPMN malignancy was originally reported to have a low incidence of between 2% and 7% in most surgical series. 16 However, more recent data suggest that the rate could be as high as 18% (from molecular pathology series) and 28% (from surgical series).…”
Section: Does Pancreatic Cyst Stability Justify Stopping Intraductal mentioning
confidence: 99%
“…One of the most significant risk factors for PCLs is age, with patients typically being diagnosed at 50 years or older and the incidence rate rising exponentially with age thereafter [ 6 , 7 , 8 , 12 ]. PCL size and number have been shown to increase with age [ 13 ]. Variations in PCL prevalence from country to country can be shown to correlate with population demographics.…”
Section: Introductionmentioning
confidence: 99%
“…While follow-up strategies for early detection of malignant degeneration of IPMN are well established on the basis of dimensional criteria, there are not screening criteria for early detection of concomitant PDAC yet. Different studies have demonstrated that IPMN is a major risk factor for PDAC (having PDAC 1% annual prevalence of concomitance with IPMN) [ 79 82 ], but some patients with IPMN have even higher risk of developing PDAC, in particular patients > 70 years and women [ 79 , 82 ], patients with benign gastric-type IPMN without guanine nucleotide-binding protein alpha-stimulating (GNAS) mutations [ 82 84 ] and patients with IPMN and family history of PDAC especially with affected first-degree relatives [ 82 , 85 , 86 ]. This group of patients should be considered at higher risk, and tailored follow-up strategies should be applied.…”
Section: Introductionmentioning
confidence: 99%
“…This follow-up strategy of course rises the big issue of a large number of asymptomatic patients overloading radiological centers, due to the high prevalence of CPLs, especially in older patients (up to 40%) [ 82 , 87 ]. To overcome this problem, an effort from multidisciplinary teams should be made in order to select patients who should undergo such a strict follow-up, not only on the basis of the potential malignant degeneration and de novo PDAC development, but also on the basis of patients’ comorbidities and operative risk.…”
Section: Introductionmentioning
confidence: 99%